2020
DOI: 10.4178/epih.e2020061
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of lifestyle, metabolic status, and obesity among hypertensive patients in Korea: a latent class analysis

Abstract: Objectives This study was conducted to identify latent classes in hypertensive patients based on the clustering of risk factors including lifestyle risk factors, metabolic risk and obesity in each sex. Methods This cross-sectional study included 102,780 male and 103,710 female hypertensive patients that underwent health checkups at 16 centers in Korea, in 2018. It was used a latent class analysis approach to identify subgroups of hypertensive patients. Multivariate logistic regression was performed to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
2
4
1
Order By: Relevance
“…On the other hand, contrary to prior studies of people without disabilities using LCA [ 7 , 10 ] a clear distinction in the self-management behaviours among groups was evident in our study. In particular, the classes exhibited stark differences with respect to physical activity (high self-management group; 100.0% vs. inactive behaviour group; 0%), although the overall probability of physical activity was not particularly different compared to previous studies [ 7 , 10 ]. Since inadequate physical activity is a well-known challenge for people with physical disabilities [ 18 ], it is important to define the characteristics and health measures among the groups.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…On the other hand, contrary to prior studies of people without disabilities using LCA [ 7 , 10 ] a clear distinction in the self-management behaviours among groups was evident in our study. In particular, the classes exhibited stark differences with respect to physical activity (high self-management group; 100.0% vs. inactive behaviour group; 0%), although the overall probability of physical activity was not particularly different compared to previous studies [ 7 , 10 ]. Since inadequate physical activity is a well-known challenge for people with physical disabilities [ 18 ], it is important to define the characteristics and health measures among the groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study has identified three mutually exclusive subgroups of hypertension self-management behaviours: a high self-management group, a harmful habitual behaviour group, and an inactive behaviour group, based on five self-management behaviours: smoking, alcohol intake, physical activity, diet, and weight control. Only 40.8% of our respondents showed adherence to the 2018 Hypertension Guidelines in their self-management of hypertension Therefore, our results extend the existing literature observations that a large proportion of patients with hypertension do not perform self-management behaviours well [ 7 , 10 , 17 ]. On the other hand, contrary to prior studies of people without disabilities using LCA [ 7 , 10 ] a clear distinction in the self-management behaviours among groups was evident in our study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations